Crenças sobre avaliação em língua inglesa: um estudo de caso a partir das metáforas no discurso de professores em formação - Maria Clara Carelli Magalhaes (2006)
A case study investigates beliefs about testing/evaluation in the discourse of four English student-teachers of a public University in the State of Minas Gerais. The beliefs held by these teachers were revealed by analyzing the metaphors they used when describing their lived/personal experiences with testing in two written narratives: One as students taking tests and the other as student-teachers giving exams to their students in the discipline English Language Teaching Practice. The metaphors expressed the ways student-teachers interpreted their previous experiences with testing. The study analyzed the influence thatprior lived experience had on their beliefs about testing and how these experiences were influential as they administered tests during the student teaching process in the Teaching Practice discipline. The results point towards a similarity in beliefs in both investigated contexts, i.e., as tested / evaluated students and in their role as testing/ evaluating teachers. In both contexts, beliefs were categorized as representing two models of belief The Experienced Testing/Evaluation Model and the Idealized Testing/Evaluation Model. The former refers to the beliefs from experiences lived in the porcess of being tested/evaluated. The latter refers to experiences with testing/evaluation that are idealized as these students reflect on their experiences in both contexts of investigation. The results confirm the idea that there is a narrow relation among experience, beliefs and actions, promoting the comprehension of student-teachers thinking about assessment and evaluation. This study also contributes to research methodology on investigating beliefs through metaphors.